2020
DOI: 10.1108/bfj-08-2019-0655
|View full text |Cite
|
Sign up to set email alerts
|

Heterogeneity in consumer preferences for ready-to-eat pomegranate: an empirical study in Italy

Abstract: PurposeThe present study aims at analysing consumer preferences for the pomegranate fruit, focussing on the effect of ready-to-eat format (i.e. packaged arils) on the purchasing choice, together with several products’ attributes as the origin, the packaging typology and the price.Design/methodology/approachThe paper presents a choice experiment (CE) among 626 Italian consumers from Veneto region through an online survey. The study estimates both a conditional logit (CL) and a latent class logit model (LCM).Fin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 56 publications
0
9
0
Order By: Relevance
“…Concerning price, our study evaluated the overall liking assigned to the different products independently from consumers' willingness to pay. Due to the relevance of price in pomegranate choice in Italy, as highlighted by Stiletto et al, 35 we expected that previous consumption experiences may lead consumers to place higher overall liking to HICAZ 39 …”
Section: Resultsmentioning
confidence: 98%
See 2 more Smart Citations
“…Concerning price, our study evaluated the overall liking assigned to the different products independently from consumers' willingness to pay. Due to the relevance of price in pomegranate choice in Italy, as highlighted by Stiletto et al, 35 we expected that previous consumption experiences may lead consumers to place higher overall liking to HICAZ 39 …”
Section: Resultsmentioning
confidence: 98%
“…The survey was administered to 203 students aged between 18 and 35 years. Since in Italy pomegranate is a product still not very widespread and little consumed in general and since young people are generally more inclined to try new products than older consumers, 35 we considered young people as target consumers, selecting students and university employees for the test.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Fuller [1] defined new food products (NFPs) as groceries that had not been presented before in any marketplace or as existing products introduced into a geographically new area or with a new package or format. In this context, pomegranate could be considered an NFP in Italy, since its cultivation has a limited (but growing) diffusion [2] and new consumption patterns of this fruit, such as ready-to-eat arils [3], have recently been spreading in the market. In the last two decades, Europe increased the import of pomegranate to about 100,000 tons, for a total value of EUR 109 million/year [4].…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, health and nutritional benefits are leading factors in purchasing choices especially for "future-oriented" [13] and young [14] consumers, and this is particularly true for pomegranate. One of the latest researches on this fruit [2], conducted in Italy in 2020, found that young consumers are the most prone to buy ready-to-eat arils, since they are the most inclined to try innovative products [15] and to adopt new consumption patterns [16].…”
Section: Introductionmentioning
confidence: 99%